Non-governmental organizations assisting victims of crime in Belgrade: Survey results - Milivojević Sanja K.; Mihić Biljana D. (Temida)
This paper presents the results of survey regarding non-governmental organizations assisting victims of crime in Belgrade. The survey was completed at the end of 2002 for purposes of establishing a Victim Support Service in Serbia. In introduction authors give a short review of victim support services development in the World and the region, explaining the need for such service in Serbia, the subject and the aim of the article as well as the purpose of the survey. Second part of the paper contains the sample, methodology and the aim of the interview with NGO representatives. In the third section authors present the analysis of the survey data. Finally, in conclusion authors summarize the data and observed problems, suggestions for possible solution and directions of future development of services and organizations assisting victims of crime in Serbia.